Evaluation of Psychological Empowerment Components in Nurses of Educational Hospitals Affiliated to Sabzevar University of Medical Sciences - Alemeh Dehnabi; Mohammad Asghari; Hamid Radsepehr (Kerman University of Medical Sciences, 2017)
Background and objectives: The ability of human resources is the most important factor in the survival of an organization. Since, hospitals are one of the important health care organizations that play an important role in returning and maintaining the physical and mental health of patients, it is essential to pay special attention to empowering staff of hospitals.The aim of this study was to assess the psychological empowerment components in nurses. Methods: This descriptive-analytic stusy was performed on 170 nurses working in hoapitals of Sabzevar University of Medical Sciences selected through stratified random sampling. Spreitzer psychological empowerment questionnaire was used to collect data. The questionnaire includes 15 questions in five dimensions of meaningfulness, self-efficacy, impact, trust and autonomy. Data were analyzed through SPSS20 and using t- test and ANOVA. Results: Mean score of psychological empowerment of nurses was 39.19±9.8. Among components of psychological empowerment, meaningfulness had the highest mean score (9.24 ±2.7) and impact had the lowest (6.11 ±2.4). Psychological empowerment showed significant relationship with sex, age, job experience, type of ward, and satisfaction of the job, the ward and the superordinate. Conclusion: The managers of educational hospitals are recommended to increase the level of empowerment indicators in their employees by identifying social processes that affect their attitudes and creating an environment that is the basis of empowerment. Keywords: Psychological empowerment, Competence, Nurses, Teaching hospitals Citation: Dehnabi A, Asghari M, Radsepehr H. Evaluation of Psychological Empowerment Components in Nurses of Educational Hospitals Affiliated to Sabzevar University of Medical Sciences. Journal of Health Based Research 2017; 3(2): 187-201.